2012
DOI: 10.1111/j.1349-7006.2012.02330.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic impact of serum‐soluble UL16‐binding protein 2 in lung cancer patients

Abstract: UL16-binding protein 2 (ULBP2) is one of the ligands for NKG2D (NKG2DL). ULBP2 expression is induced in transformed cells and is recognized by immune effector cells via the activating NKG2D immunoreceptor. Soluble forms of NKG2DL have been reported in the serum of patients with several types of cancer. The present study investigated the diagnostic and prognostic significance of serum-soluble ULBP2 (sULBP2) in lung cancer patients. We used flow cytometry to evaluate the surface expression of NKG2DL by various l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 47 publications
2
29
1
Order By: Relevance
“…Similarly, Cho et al showed that m-ULBP1–5 were all expressed in cervical cancer tissue and that m-ULBP1 was an independent predictor of good prognosis regarding both DFS and OS 19. Yamaguchi et al demonstrated that s-ULBP2 was useful in the diagnosis of squamous cell carcinoma and could be considered a prognostic indicator for patients with advanced non-small-cell lung cancer 38. However, not all experiments were consistent with our results 21,39.…”
Section: Discussionsupporting
confidence: 69%
“…Similarly, Cho et al showed that m-ULBP1–5 were all expressed in cervical cancer tissue and that m-ULBP1 was an independent predictor of good prognosis regarding both DFS and OS 19. Yamaguchi et al demonstrated that s-ULBP2 was useful in the diagnosis of squamous cell carcinoma and could be considered a prognostic indicator for patients with advanced non-small-cell lung cancer 38. However, not all experiments were consistent with our results 21,39.…”
Section: Discussionsupporting
confidence: 69%
“…The presence of sMICA in Stage III and IV PDAC patient sera and the accompanying downregulation of NKG2D receptor on NK cells revealed both parameters to be independent markers of pancreatic malignant disease progression 32 . Similarly, elevated sMICB or sULBP2 levels in sera have also been associated with worse outcome, including sMICB in late-stage oral squamous cell carcinoma (OSCC) 38 and melanoma patients, 39 and sULBP2 among melanoma 35 and NSCL patients 37 …”
Section: Soluble Nkg2dl In Tumor Cellsmentioning
confidence: 98%
“…Unlike MICA, little is known about the presence of other ligands in solid cancers. High levels of soluble MICB (sMICB) have been observed in PDAC patient sera 33 and in the culture media supernatant of human cervical cancer cell lines, 36 whereas elevated soluble ULBP2 (sULBP2) has been detected in melanoma 35 and non-small cell lung cancer (NSCL) patients 37 …”
Section: Soluble Nkg2dl In Tumor Cellsmentioning
confidence: 99%
“…Shedding of other family of NKG2D ligands, such as ULBP2 has also been reported to correlate with poor prognosis in selected cancer of solid tumors and hematological malignancies [4852]. Most recent clinical studies in cohorts of melanoma patients suggested that baseline serum soluble NKG2D ligands may negatively impact clinical outcome of immune checkpoint blockade therapy [10 ● ].…”
Section: Nkg2d Ligands In Human Cancermentioning
confidence: 99%